You Are What You (First) Eat - Buchanan, Kelly L.; Bohórquez, Diego V. (Frontiers in Human Neuroscience, 2018)
As far back as we can remember, we eat. In fact, we eat before we can remember. Our first meal is amniotic fluid. We swallow it during the first trimester of gestation, and with that we expose our gut to a universe of molecules. These early molecules have a profound influence on gut and brain function. For example, the taste of the amniotic fluid changes based on the mother's diet. Indeed, recent findings suggest that food preferences begin in utero. Likewise, a baby's first exposure to bacteria, previously thought to be during birth, appears to be in utero as well. And just as postnatal food and microbiota are implicated in brain function and dysfunction, prenatal nutrients and microbes may have a long-lasting impact on the development of the gut-brain neural circuits processing food, especially considering their plasticity during this vulnerable period. Here we use current literature to put forward concepts needed to understand how the gut first meets the brain, and how this encounter may help us remember food.